Effect of essential oils on meat and fat qualities of crossbred young bulls finished in feedlots - Rivaroli, Dayane Cristina [UNESP]; Guerrero, Ana; Valero, Maribel Velandia; Zawadzki, Fernando; Eiras, Carlos Emanuel; del Mar Campo, Maria; Sanudo, Carlos; Jorge, Andre Mendes [UNESP]; Prado, Ivanor Nunes do (Elsevier B.V., 2016)
Twenty-seven animals (1/2Angus - 1/2 Nellore) were fed for four months with one of the following diets: without addition of essential oils (E0.0), with 3.5 (E3.5) or 7 (E7.0) g/animal/day of an essential oil blend (oregano, garlic, lemon, rosemary, thyme, eucalyptus and sweet orange). Chemical composition, fatty add profile and meat color were evaluated in Longissimus muscle. In addition, the effects of aging (one, seven and 14 days) on the meat water holding capacity, texture and lipid oxidation were evaluated. Essential oils had no effect on chemical and fatty acid composition, meat color, water holding capacity or texture, but an inclusion of 3.5 g/day decreased lipid oxidation. The addition of 7.0 g/animal/day had a pro-oxidant effect on meat during aging and resulted in higher values for lipid oxidation at 14 days of aging. Aging significantly affected thawing losses and texture. A dose of 3.5 g/animal/day could be recommended in feedlot animals, but greater doses could have a pro -oxidant effect. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Antioxidant effect; Aging; Beef; Fatty acid composition; High-concentrate system; Natural additives